Heterogeneity of T-Tubules in Pig Hearts. - Hanne C Gadeberg; Richard C Bond; Cherrie H T Kong; Guillaume P Chanoit; Raimondo Ascione; Mark B Cannell; Andrew F James (PLoS ONE)
Background T-tubules are invaginations of the sarcolemma that play a key role in excitation-contraction coupling in mammalian cardiac myocytes. Although t-tubules were generally considered to be effectively absent in atrial myocytes, recent studies on atrial cells from larger mammals suggest that t-tubules may be more numerous than previously supposed. However, the degree of heterogeneity between cardiomyocytes in the extent of the t-tubule network remains unclear. The aim of the present study was to investigate the t-tubule network of pig atrial myocytes in comparison with ventricular tissue. Methods Cardiac tissue was obtained from young female Landrace White pigs (45-75 kg, 5-6 months old). Cardiomyocytes were isolated by arterial perfusion with a collagenase-containing solution. Ca2+ transients were examined in field-stimulated isolated cells loaded with fluo-4-AM. Membranes of isolated cells were visualized using di-8-ANEPPS. T-tubules were visualized in fixed-frozen tissue sections stained with Alexa-Fluor 488-conjugated WGA. Binary images were obtained by application of a threshold and t-tubule density (TTD) calculated. A distance mapping approach was used to calculate half-distance to nearest t-tubule (HDTT). Results & conclusion The spatio-temporal properties of the Ca2+ transient appeared to be consistent with the absence of functional t-tubules in isolated atrial myocytes. However, t-tubules could be identified in a sub-population of atrial cells in frozen sections. While all ventricular myocytes had TTD >3% (mean TTD = 6.94±0.395%, n = 24), this was true of just 5/22 atrial cells. Mean atrial TTD (2.35±0.457%, n = 22) was lower than ventricular TTD (P<0.0001). TTD correlated with cell-width (r = 0.7756, n = 46, P<0.0001). HDTT was significantly greater in the atrial cells with TTD ≤3% (2.29±0.16 μm, n = 17) than in either ventricular cells (1.33±0.05 μm, n = 24, P<0.0001) or in atrial cells with TTD >3% (1.65±0.06 μm, n = 5, P<0.05). These data demonstrate considerable heterogeneity between pig cardiomyocytes in the extent of t-tubule network, which correlated with cell size.